2016
DOI: 10.1097/rlu.0000000000000922
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive 131I Uptake in a Benign Bone Lesion on Post-therapy Scan

Abstract: A 56-year-old woman underwent near-total thyroidectomy and papillary thyroid carcinoma without extrathyroidal extension was diagnosed. The serum thyroglobulin (Tg) level was 2.4 µg/L, and anti-Tg was negative when serum thyroid-stimulating hormone level was 85 µIU/mL. She received 100 mCi (3.7 GBq) of 131I. Besides the residual thyroid tissue, a focal uptake in the left clavicular bone was seen on posttherapy 131I images. Then, CT and MRI were performed to diagnosis. All imaging findings suggested that it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Focal I-131 uptake of one case was located to the clavicle. This patient has been reported as a case-report earlier, in whom the focal I-131 uptake corresponded to a hypodense area in the left clavicle on CT images ( 4 ). An MRI revealed that the finding belonged to a benign lesion, a simple bone cyst.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Focal I-131 uptake of one case was located to the clavicle. This patient has been reported as a case-report earlier, in whom the focal I-131 uptake corresponded to a hypodense area in the left clavicle on CT images ( 4 ). An MRI revealed that the finding belonged to a benign lesion, a simple bone cyst.…”
Section: Resultsmentioning
confidence: 53%
“…Radioiodine enters cysts by passive diffusion and is trapped in the cyst ( 8 ). In this paper, a case with I-131 accumulation due to a benign bone cyst in the clavicle is also included, who has been previously reported ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reported cases of false-positive radioiodine uptake in tissues other than ovary, such as bone tissue [ 8 ], hepatic hydatid cyst [ 9 ] and parapelvic renal cyst [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent of the patient was obtained for all procedures. Many false-positive findings in I-131 scans due to physiological variants, inflammation or some non-thyroidal neoplasms have been reported (4,5,6,7,8). As a result, the following interesting/ rare situations were seen in combination in this case: false-positive I-131 uptakes at wedge-resection site and soft tissues, false-negative I-131 for FDGavid lymph metastasis, and detection of metastases after 12 years of disease-free follow-up that emphasizes the importance of long term follow-up.…”
mentioning
confidence: 99%